Forecasting land surface deformation in Ha Dong region due to urbanization and exploitation of groundwater - Tư, Trần Văn; Anh, Hà Ngọc; Đức, Đào Minh; Tùng, Nguyễn Mạnh (Vietnam Journal of Earth Sciences, 2013)
A huge surface deformation is present firstly the existence of the weak soil layers existing in the region, the second is construction plans which are not reasonable and, the third is exploitation of underground water more and more over.But the consequences are all due to the first cause. The weak soil layers in Hadong region are formed mainly by marine transgression in early and middle Holocene stages. It was muddy sediments of coastal bays or lakes with high organic compounds and in flow state. The soil layers with high deformation caused land surface subsidence when loading. It is special dangerous due to nonconformity between spatial distribution of weak soil layer and the loading forms. This paper 35 presents the results calculated by the finite element method (FEM) to predict ground deformation in HaDong region with the different surface loads and underground water exploitation.The exploitation of groundwater in the large and small scale in this region is now a topical issue. Groundwater level falls down for Hanoi city by monitoring network wells. At the same time, many parts of the city show land subsidence by topography repeat measurements. Main cause of falling down groundwater level is the groundwater exploitation withoutplanning by private households businesses. Exploitation amount of groundwater is more than water supplied caused groundwater levels decline and lead to ground subsidence in weakness areas of soil layers.There is necessary of ground deformation and groundwater level monitoring for ground subsidence and deformation forecasting to urban planning and territorial security constructing for Hanoi city